Destabilization and Mislocalization of Myelin Basic Protein mRNAs in quaking Dysmyelination Lacking the QKI RNA-Binding Proteins - Li, Zhenzhong (J Neurosci, 2000)
Quakingviable (qk(v)) is a well known dysmyelination mutation. Recently, the genetic lesion of qk(v) has been defined as a deletion 5′ to the qkI gene, which results in the severe reduction of the qkI-encoded QKI RNA-binding proteins in myelin-producing cells. However, no comprehensive model has been proposed regarding how the lack of QKI leads to dysmyelination. We hypothesized that QKI binds to myelin protein mRNAs, and the lack of QKI causes posttranscriptional misregulation, which in turn leads to the loss of the corresponding myelin proteins. To test this hypothesis, we developed an RNase protection assay to directly measure the mRNA isoforms encoding the myelin basic proteins (MBPs) in the brain. Our result suggested that isoform-preferential destabilization of MBP mRNAs in the cytoplasm was responsible for the reduced MBPs in the qk(v)/qk(v) brain during early myelination. In addition, we detected markedly reduced MBP mRNAs in the qk(v)/qk(v) myelin fraction with concomitant accumulation of MBP mRNAs associated with membrane-free polyribosomes. Presumably, the impaired localization of MBP mRNAs to the myelin membrane may cause insufficient incorporation of the newly synthesized MBPs into the myelin sheath. Finally, we observed interactions between QKI and MBP mRNAs, and removing MBP 3′UTR significantly reduced QKI-binding. Taken together, these observations suggest that misregulation at multiple posttranscriptional steps is responsible for the severe reduction of MBPs in qk(v)dysmyelination, presumably because of the lack of interactions between MBP mRNAs and the QKI RNA-binding proteins.